O silenciamento, a resistência feminina e a constituição simbolista de Flora, por Machado de Assis - Cristiane de Mesquita Alves; José Guilherme de Oliveira Castro (Revista Odisséia, 2025)
The aim of this article is to interpret the profile of the character Flora, from Machado de Assis' penultimate novel Esaú e Jacó, from the perspective of the literary characteristics corresponding to Symbolism, especially with regard to the nefelibata character elaborated to describe the a priori, silenced and indecisive female identity presented by her and how her behavior contributes to promoting an action of resistance to patriarchy, especially in relation to the obligation of marriage. To this end, the research was based on literature reviews of certain concepts about this aesthetic movement, based on different theoretical assumptions, in order to support the argument throughout the study that proposed reading the character, belonging to a text from the writer's second phase (realist), as symbolist.